2022
DOI: 10.3892/ijo.2022.5336
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role of radiation‑induced exosomes in hepatocellular carcinoma progression and radioresistance (Review)

Abstract: The incidence rates of hepatocellular carcinoma (HCC) worldwide are increasing, and the role of radiotherapy is currently under discussion. Radioresistance is one of the most important challenges in the therapy of HCC compared with other local advanced, recurrent and metastatic cancers. The mechanisms of radioresistance are complex and remain to be fully understood; however, extracellular vesicles have been investigated in recent studies. Exosomes, which are 40-to 150-nm extracellular vesicles released by canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“… 36 For patients receiving radiotherapy, radioresistance is one of the most important challenges in the management of HCC. 12 In the present study, we demonstrated the feasibility of BNCT to overcome the radioresistance of HCC. BNCT efficiently eliminated HepG2-R cells, which resisted γ-ray irradiation at the same dose.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“… 36 For patients receiving radiotherapy, radioresistance is one of the most important challenges in the management of HCC. 12 In the present study, we demonstrated the feasibility of BNCT to overcome the radioresistance of HCC. BNCT efficiently eliminated HepG2-R cells, which resisted γ-ray irradiation at the same dose.…”
Section: Discussionsupporting
confidence: 50%
“… 9 , 10 Moreover, the effectiveness of RT can be compromised by radioresistance. 11 , 12 Although immunotherapy has emerged as a breakthrough in HCC treatment, there are still some challenges, such as the low response rate, uncertain efficacy, and side effects. 13 , 14 Consequently, it is necessary to develop an effective therapy for recurrent advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
“… Principles and applications of sEVs in cancer therapy. ( a ) sEV contents induce chemo [ 14 ], radiation [ 16 ], and targeted therapy resistance [ 17 ] by changing the sensitivity of recipient cells through intercellular communication; ( b ) sEVs can regulate angiogenesis [ 17 , 18 ] and vascular permeability [ 19 , 20 ] by influencing the behavior of endothelial cells that line blood vessels; ( c ) sEVs can regulate the evasion [ 21 ] and infiltration [ 22 ] of immune cells by stimulating or suppressing immune responses, that is, they have the ability to act as immunomodulators [ 23 ]; ( d ) direct incubation of sEVs with cargo [ 24 ] or sEVs with surface engineering [ 25 ] can achieve the function of therapeutic cargo packing and targeted therapy (Created with (accessed on 26 February 2023)). …”
Section: Figurementioning
confidence: 99%
“…The mechanisms underlying radioresistance are complex, involving various factors such as radiation-induced DNA damage repair, apoptosis escape, cell cycle arrest, abnormal autophagy, abundance of cancer stem cells, and other dysregulated biological processes [61] . Radioresistance is also highly associated with TME, a critical factor influencing tumor progression and therapeutic response, which can be modulated through intercellular communications mediated by exosomes [62,63] .…”
Section: Exosomes Mediate Radioresistance In Radiotherapy Of Hccmentioning
confidence: 99%